Low-Temperature Pd/Zeolite Passive NOx Adsorbers: Structure, Performance, and Adsorption Chemistry - Zheng, Yang; Kovarik, Libor; Engelhard, Mark H; Wang, Yilin; Wang, Yong; Gao, Feng; Szanyi, János (Journal of physical chemistry. C, 2017)
Pd/zeolite passive NOₓ adsorber (PNA) materials were prepared with solution ion-exchange between NH₄/zeolites (Beta, ZSM-5, and SSZ-13) and PdCl₂ solutions. The nature of Pd (dispersion, distribution, and oxidation states) in these materials was characterized with Na⁺ ion exchange, TEM imaging, CO titration with FTIR, and in situ XPS. The NOₓ trapping and release properties were tested using feeds with different compositions. It is concluded that multiple Pd species coexist in these materials: atomically dispersed Pd in the cationic sites of zeolites and PdO₂ and PdO particles on the external surfaces. While Pd is largely atomically dispersed in ZSM-5, the small pore opening for SSZ-13 inhibits Pd diffusion such that the majority of Pd stays as external surface PdO₂ clusters. NOₓ trapping and release are not simple chemisorption and desorption events but involve rather complex chemical reactions. In the absence of CO in the feed, cationic Pd(II) sites with oxygen ligands and PdO₂ clusters are reduced by NO to Pd(I) and PdO clusters. These reduced sites are the primary NO adsorption sites. In the presence of H₂O, the as-formed NO₂ desorbs immediately. In the presence of CO in the feed, metallic Pd, “naked” Pd²⁺, and Pd⁺ sites are responsible for NO adsorption. For Pd adsorption sites with the same oxidation states but in different zeolite frameworks, NO binding energies are not expected to vary greatly. However, NO release temperatures do vary substantially with different zeolite structures. This indicates that NO transport within these materials plays an important role in determining release temperatures. Finally, some rational design principles for efficient PNA materials are suggested.